RESEARCH MAPPING ON CREDIT RISK IN ISLAMIC AND CONVENTIONAL BANKING - Budianto, Eka Wahyu Hestya (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
This study aims to determine the development of research around credit risk in Islamic and Conventional Financial Institutions. The research was conducted from 1975 to 2022 by searching national and international journals indexed by Google Scholar, Sinta, and Scopus via the Perish/Harzing application with the keyword